Pengaruh Pemberian Kompres Bubuk Jahe Merah Terhadap Nyeri Pada Lansia Dengan Gout Arthtritis - Putri, Ghea Indah; Rahmiwati, Rahmiwati; Yesti, Yulia (Universitas Fort De Kock Bukittinggi, 2021)
Background: Gout was once called the king of disease and disease of king. Ordinary people call it gout. Gout is a metabolic disease caused by excess levels of uric compounds in the body, either due to overproduction, inadequate elimination, or increased purine intake. This study aims to determine the effect of giving red ginger powder compresses to pain in the elderly with gout arthritis. Methods: This study used the Quasy Experiment design with the design used was the pretest-posttest control group design. Results: The results showed that there was a significant effect of giving red ginger powder on pain in the elderly with Gout Arthritis (p-value = 0.000). The Respondents 'Pain Scale Before Giving Ginger Powder Compress with a mean = 4.20 and there was a decrease in the Respondents' Pain Scale after Ginger Powder Compress was given with a mean = 2.30. Conclusion: It can be concluded that the administration of red ginger powder compresses can reduce pain in the elderly. Therefore, it is advisable for gout arthritic patients to take advantage of red ginger powder compresses as an effort to control gout arthritis.Keywords: Pain, Gout Arthritis, Red ginger powder compress, Elderly